PERBEDAAN TINGKAT PENGETAHUAN DAN SIKAP TENTANG HIV/AIDS PADA WARIA PEKERJA SEKS KOMERSIAL DAN WARIA NON-PEKERJA SEKS KOMERSIAL DI KOTA MANADO - Awad, Laila; Elim, Christofel; Dundu, Anita E.; Ekawardani, Neni (e-CliniC, 2015)
Abstract: HIV/AIDS is a health problem that is threatening the world, including Indonesia. Manado has a high prevalence of HIV/AIDS in North Sulawesi with numbers of cases of 101 patients with HIV and 212 patients with AIDS in 2011. According to the group transmission, transvestites belong to the second rank of high risk group spreaders of HIV/AIDS due to the transvestites sex life impact. This was an observational analytical study with a cross sectional design. Samples were obtained by using the purposive sampling technique. We used questionnaire to be filled by 60 transvestites and a qualitative study on 2 transvestites to obtain more accurate data. The collected data were analyzed by using SPSS 20.0. The Mann-Whitney statistical test showed that there was a significant difference of knowledge between Transvestites Commercial Sex Workers and Transvestites Non-Commercial Sex Workers (p <0.05). The significant value was due to the difference of attitudes between Transvestite Commercial Sex Workers and Transvestite Non-Commercial Sex Workers (p <0.05).Keywords: knowledge, attitude, HIV/AIDS, transvestite commercial sex worker, transvestite non-commercial sex workerAbstrak: HIV/AIDS merupakan masalah kesehatan yang masih mengancam dunia termasuk Indonesia hingga saat ini. Manado merupakan kota dengan prevalensi HIV/AIDS tertinggi di Sulawesi Utara dengan jumlah kasus 101 pasien HIV dan 212 pasien AIDS pada tahun 2011. Menurut kelompok penularannya, waria menduduki urutan kedua sebagai kelompok resiko tinggi penyebar HIV/AIDS akibat dari dampak kehidupan seks kaum waria. Penelitian ini besifat analitik observasional dengan pendekatan Cross-Sectional dengan teknik pengambilan sampel yaitu Purposive Sampling. Penelitian ini dilakukan dengan menggunakan kuisioner kepada 60 waria dan dilanjutkan dengan penelitian kualitatif terhadap 2 orang waria untuk memperoleh data yang lebih akurat. Data yang diperoleh diolah dengan SPSS 20.0. Hasil pengolahan data menggunakan analisis statistik Mann-Whitney menunjukkan nilai signifikan adanya perberdaan tingkat pengetahuan antara Waria PSK dan Waria Non-PSK (p<0,05). Nilai yang signifikan diperoleh dengan adanya perbedaan sikap antara Waria PSK dan Waria Non-PSK (p<0,05).Kata kunci: pengetahuan, sikap, HIV/AIDS, waria PSK, waria non-PSK